The Celts : A History From Earliest Times to the Present - Maier, Bernhard (Edinburgh University Press, 2017)
Now in its second edition, this comprehensive history of the Celts draws on archaeological, historical, literary and linguistic evidence to provide a comprehensive and colourful overview from origins to the present.